Society and circulation : mobile people and itinerant cultures in South Asia, 1750-1950 - Markovits, Claude; Pouchepadass, Jacques; Subrahmanyam, Sanjay (Delhi : Permanent Black ; Bangalore : Distributed by Orient Longman, 2003)
Contributed articles.
Keywords: Occupational mobility -- South Asia; Transnationalism; Nomads -- South Asia